2020
DOI: 10.1016/j.omtn.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0001955 Enhances In Vitro Proliferation, Migration, and Invasion of HCC Cells through miR-145-5p/NRAS Axis

Abstract: Increasing circular RNAs (circRNAs) have been reported to act as key players in human malignancies. However, the expression, role, and mechanism of circRNAs in HCC are not well elucidated. In this study, some differentially expressed circRNAs (DECs) between hepatocellular carcinoma (HCC) and normal tissues were identified using three circRNA microarrays (Gene Expression Omnibus [GEO]: GSE78520, GSE94508, and GSE97332). Twenty-one DECs were found to be commonly upregulated in all the three datasets. Among the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 26 publications
2
57
0
Order By: Relevance
“…We found that there were 5 overlapping circRNAs (hsa_circ_0067934, hsa_circ_0003528, hsa_circ_0001955, hsa_circ_0008274, and hsa_circ_0072088) in the top 50 upregulated circRNAs in the GSE78520 and GSE94508 microarray datasets (Figure 1A). Among the 5 overlapping circRNAs, the biological role of hsa_circ_0067934 [27], hsa_circ_0001955 [28], hsa_circ_0008274 [29], and hsa_circ_0072088 [30] in HCC had been verified. Thus, we choose hsa_circ_0003528 for further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…We found that there were 5 overlapping circRNAs (hsa_circ_0067934, hsa_circ_0003528, hsa_circ_0001955, hsa_circ_0008274, and hsa_circ_0072088) in the top 50 upregulated circRNAs in the GSE78520 and GSE94508 microarray datasets (Figure 1A). Among the 5 overlapping circRNAs, the biological role of hsa_circ_0067934 [27], hsa_circ_0001955 [28], hsa_circ_0008274 [29], and hsa_circ_0072088 [30] in HCC had been verified. Thus, we choose hsa_circ_0003528 for further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…By knocking down the expression of ESRP2 in the HCC model cell line Huh-7, we observed a significant upregulation of three circRNAs (hsa_circ_0001955, hsa_circ_0008016, and hsa_circ_0008274). These circRNAs are upregulated in HCC, and the oncogenic role in HCC was already confirmed for two [ 48 , 49 ]. Since these circRNAs are upregulated after ESRP2 knockdown in cell lines, this indicates that ESRP2 could inhibit the biogenesis of these circRNAs in the liver.…”
Section: Discussionmentioning
confidence: 95%
“…CircRNAs are involved in the development of various cancers 12–14 . In HCC, a previous study demonstrates that circ_0001955 expression is upregulated, and knockdown of circ_0001955 markedly inhibits the proliferation, migration, and invasion of HCC cells 15 . Another study reports that circRNA_103809, whose expression is dysregulated in HCC, can promote HCC development by regulating miR‐377‐3p/EGFR1/ERK axis 16 .…”
Section: Discussionmentioning
confidence: 99%